Low-Contrast High-Pass Visual Acuity Might Help to Detect Glaucoma Damage: A Structure-Function Analysis - Wen, Yun; Chen, Zidong; Zuo, Chengguo; Yang, Yangfan; Xu, Jiangang; Kong, Yang; Cheng, Hui; Yu, Minbin (Frontiers in Medicine, 2021)
Purpose: The conventional visual acuity (VA) test is not sensitive for detecting glaucoma macular damage. We aimed to investigate whether VA measurements using low-contrast high-pass optotypes are more sensitive to macular dysfunction in glaucoma and to find the potential structural basis of this difference. Methods: A total of 147 subjects were recruited, including 118 patients with glaucoma (mean age: 46.08 ± 14.64 years) and 29 healthy controls (mean age: 39.83 ± 9.81 years). For each participant, monocular best-corrected VA was measured using a conventional chart and six high-pass charts at 100%, 50%, 10%, 5%, 2.5%, and 1.25% contrast levels respectively. The macular retinal thickness and circumpapillary retinal nerve fiber layer (cpRNFL) thickness of all glaucoma subjects were obtained by spectral-domain optical coherence tomography (SD-OCT). Results: Compared with healthy subjects, glaucoma patients with normal vision demonstrated worse VAs in high-pass acuity measurements (0.22 to 0.93 vs. 0.28 to 1.08, p < 0.05). Receiver operating characteristic curve (ROC) showed that 1.25% low-contrast high-pass VA was optimal for discriminating between controls and glaucoma (AUC: 0.918, p < 0.001; sensitivity: 77.33%; specificity: 96.55%). Compared with conventional VA, 1.25% high-pass VA correlated better with nasal-side macular retinal ganglion cell (RGC)-related parameters (r = -0.419 to -0.446 vs. r = -0.538 to -0.582; Fisher’s Z transformation, pz < 0.05). There is no difference in the strength of correlations between VAs measured using different charts and cpRNFL thickness (Fisher’s Z transformation; pz > 0.05). Conclusions: VA measurement taken with low-contrast (1.25%) high-pass acuity chart is more sensitive in detecting central visual loss in glaucoma than that taken with the conventional chart. Macular RGC damage appears to be associated with low-contrast (1.25%) high-pass visual loss in glaucomatous eyes.